Susceptibility Of Root Canal Flora To Chitosan, Chlorhexidine And Their Combination - An In Vitro Study (Journal of Pharmaceutical Negative Results, 2022)
Introduction: The aim of the study was to evaluate the antimicrobial effect of chitosan, chlorhexidine, and their combination, on root canal flora. Method: Antimicrobial efficacy was evaluated using the agar-well diffusion method. Ten samples of each ATCC strain i.e. Enterococcus faecalis, Candida albicans, Staphylococcus aureus, Pseudomonas aeruginosa and Streptococcus sanguis were examined for antimicrobial efficacy of 2% chlorhexidine, 2% chitosan and their combination.Results: There was no statistically significant difference in zones of inhibition between chlorhexidine and chlorhexidine+chitosan against different microorganisms(p>0.05). Normal saline and chitosan alone did not show any zones of inhibition.Conclusion: No statistically significant difference was found between the antimicrobial efficacy of chlorhexidine and chlorhexidine+chitosan against different microorganisms.